2021
DOI: 10.3389/fnins.2021.730322
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Studies of Acupuncture on Low Back Pain: A Systematic Review

Abstract: Objectives: This study was conducted in order to investigate the study design and main outcomes of acupuncture neuroimaging studies on low back pain (LBP).Methods: Neuroimaging studies of acupuncture on LBP were collected from three English databases such as PubMed and four Chinese databases such as China National Knowledge Infrastructure (CNKI) from inception to December 31, 2020. Study selection, data extraction, and assessment of risk of bias were performed independently by two investigators. The quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The improvements of symptoms in CSAP patients induced by acupuncture were associated with its multi-targeted modulations of the pain process. These similar results have also been observed in acupuncture treatment of other visceral pains and somatalgia ( Ma et al, 2020 , 2021 ; Wen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…The improvements of symptoms in CSAP patients induced by acupuncture were associated with its multi-targeted modulations of the pain process. These similar results have also been observed in acupuncture treatment of other visceral pains and somatalgia ( Ma et al, 2020 , 2021 ; Wen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…You et al (60) reported alterations in DMN hub configurations following acupuncture at ST36. A meta-analysis of acupuncture for low back pain revealed that the brain regions involved in acupuncture were located in the salience network, DMN, pain matrix, and descending pain modulatory system (61), demonstrating the analgesic effect of acupuncture. The DMN is associated with several advanced cognitive functions; the salience network mediates the switching between the DMN and the central executive network, and those three networks are theoretically the core "triple networks" in cognition.…”
Section: Discussionmentioning
confidence: 99%
“… 24 A neuroimaging systematic review suggested that acupuncture improved the abnormal brain structure and functional activity in patients with low back pain (LBP) mainly through the pain matrix, default mode network (DMN), salience network (SN), and descending pain modulatory system (DPMS). 25 Tu et al found that neural markers of abnormal connectivity in the visual, default mode, sensorimotor, and frontal-parietal networks captured the unique features of migraine without aura (MwoA), and that changes in marker showed a significant correlation with changes in headache frequency during TA treatment. 26 Neuroimaging studies of acupuncture showed that true acupuncture activates the insula and thus increases the pain threshold significantly compared to controls.…”
Section: Introductionmentioning
confidence: 99%